Drafting Assistance On Traditional Jamu UMKM - Murniati, Wahyuning (IMPOWERMENT SOCIETY, 2020)
Patent Drafting is a method for preparing patent documents. As it is known, UMKM Jamu is engaged in the health sector by producing traditional herbal medicine which is believed to be effective in preventing the growth of cancer cells and various other diseases. UMKM located in Wonorejo Village, Lumajang Regency, need patent drafting assistance for the preparation of patent documents. Therefore, this assistance is carried out with the aim of providing understanding to the UMKM Jamu Ibuk producers regarding patents. The output of this activity is a patent document ready to register. With this activity, it is hoped that it can provide thoughts on the importance of protecting Intellectual Property for MSMEs and the wider community.